Incorporating bioenergy into sustainable landscape designs. (April 2016) - Dale, Virginia H.; Kline, Keith L.; Buford, Marilyn A.; Volk, Timothy A.; Tattersall Smith, C.; Stupak, Inge
Abstract: The paper describes an approach to landscape design that focuses on integrating bioenergy production with other components of environmental, social and economic systems. Landscape design as used here refers to a spatially explicit, collaborative plan for management of landscapes and supply chains. Landscape design can involve multiple scales and build on existing practices to reduce costs or enhance services. Appropriately applied to a specific context, landscape design can help people assess trade-offs when making choices about locations, types of feedstock, transport, refining and distribution of bioenergy products and services. The approach includes performance monitoring and reporting along the bioenergy supply chain. Examples of landscape design applied to bioenergy production systems are presented. Barriers to implementation of landscape design include high costs, the need to consider diverse land-management objectives from a wide array of stakeholders, up-front planning requirements, and the complexity and level of effort needed for successful stakeholder involvement. A landscape design process may be stymied by insufficient data or participation. An impetus for coordination is critical, and incentives may be required to engage landowners and the private sector. Hence devising and implementing landscape designs for more sustainable outcomes require clear communication of environmental, social, and economic opportunities and concerns.